Curcumin-Loaded Nanoemulsion for Better Cellular Permeation - Nur Hulwani Md Saari; Lee Suan Chua; Rosnani Hasham; Leny Yuliati (MDPI AG, 2020)
Curcumin nanoemulsion was prepared using coconut oil, Tween 80 (surfactant) and polyethylene glycol (co-solvent) with the addition of honey and glycerol as additives. The nanoemulsion was optimized and systematically characterized for transdermal delivery. Small particle size (15.92 nm), low polydispersity index (0.17) and slight acidic (pH 4.18) curcumin nanoemulsion was obtained without any chemical degradation based on the Fourier transform infrared (FTIR) spectrum. The incorporation of curcumin inside nanoglobul improved curcumin stability and skin permeability. Its high permeability can be seen from Nile dyed curcumin in different layers of skin through fluorescent imaging. The release kinetic of curcumin followed the Higuchi model, which explains why the skin permeation was a Fickian diffusion-controlled process because the Korsmeyer constant was proven to be 0.3 (<0.5). Nanoencapsulation slightly decreased the antioxidant capacity of curcumin for about 7.9% compared to its free counterpart. It showed low cytotoxicity (EC50 2.3552 µg/mL) to human skin fibroblasts. Cell death was noticed at a high concentration (2.5 µg/mL) of treatment. Curcumin was also found to promote wound closure at low concentration 0.1563 µg/mL and was comparable with the performance of ascorbic acid based on scratch assay. Therefore, this nutritious curcumin nanoemulsion is a promising transdermal delivery system for topical application.